Houston Enhanced Action Patrol: Examining the Effects of Differential Deployment Lengths with a Switched Replication Design. (15th April 2016) - Hoover, Larry; Wells, William; Zhang, Yan; Ren, Ling; Zhao, Jihong
Abstract : Studies have tested variations of concentrated patrol combined with intense field interrogations, broken windows enforcement, Compstat accountability, and problem-oriented approaches. Although a majority of findings support the efficacy of concentrated patrol, a substantial number do not. Questions remain regarding six variables: dimension, dosage, duration, displacement, diffusion, and denouement. This study tested differential deployment lengths of geographically concentrated, proactive patrol for an additional 80 h per week in 13 high crime beats in Houston, TX. The original purpose was to identify optimal lengths of deployment periods. The study used a switched replication design with repeated treatments over deployment periods ranging from 4 to 12 weeks. Meaningful reductions in suppressible street crime occurred in only 2 of the 13 beats. The two beats were among the smallest, had among the highest crime rates, and received the highest dosage of concentrated patrol.